School of the future - Bertelsen, Phil; Teeling, Jane; PBS Distribution (Firm); Ark Media (Firm); Realization Pictures (Arlington, VA : PBS Distribution, 2016)
In a new age of information, rapid innovation, and globalization, how can children be prepared to compete? Discover how the new science of learning can help reimagine the future of education for all children.
DVD; Widescreen (16x9) presentation; Stereo; Region 1.
English subtitles for the deaf and hard of hearing.
Widescreen (16x9)
Originally broadcast by PBS Sept. 14, 2016.
Grade level: High school (9-12)
LeVar Burton, narrator.
Keywords: Education -- United States; Educational change -- United States; Education -- United States; Educational change -- United States; Educational change -- United States -- Juvenile films; Educational change -- United States; Documentary television programs; Nonfiction television programs; Video recordings for the hearing impaired; Television series; Children's television programs; Video recordings for the hearing impaired; Nonfiction television programs